DIGITAL MARKETING DAN PERANAN ELECTRONIC WORD OF MOUTH SERTA INOVASI PRODUK PARIWISATA PENGARUHNYA TERHADAP LOYALITAS WISATAWAN DI MUSEUM GEOPARK BATUR KINTAMANI - Luh Kadek Budi Martini; Ni Putu Widiastuti; Komang Sri Wahyuni Prabawathi (Journal of Applied Management Studies, 2023)
Batur Geopark is a geological tourism area located in Bangli Regency, Bali. This area is famous for its natural beauty, including Mount Batur which is the icon of the area. Another thing that attracts destinations in this area is the Batur Geopark Museum. Batur Geopark has long been a popular tourist destination. With this popularity, the visits to this destination area are quite high. Likewise, with the Batur Geopark Museum. With the high intention of tourists to visit, it is necessary to make efforts to maintain tourist loyalty. The purpose of this study was to analyze the effect of digital marketing, e-word of mouth, product innovation on the loyalty of Batur Geopark museum tourists. The location of this research is the Batur Kintamani Geopark Museum located on Jalan Raya Penelokan, Kintamani, Bangli, Bali Province. The method of determining the sample using random sampling with the slovin formula, with a total sample of 100 respondents. The data collection method in this study used a questionnaire with a scale likert (5 scale). The data analysis technique used is multiple linear regression analysis. The results showed that digital marketing has a positive and significant effect on tourist loyalty. The role of e-WOM has a positive and significant effect on tourist loyalty. Tourism product innovation has a positive and significant effect on tourist loyalty. Digital marketing, the role of e-WOM and tourism product innovation have a positive and significant effect on tourist loyalty.